DANCE THERAPY-METHOD MARIA FUX CONTRIBUTIONS IN THE LIFE OF MODERN WOMAN (Fiep Bulletin - online, 2017)
This article refers to the work on stage in dance therapy - method Maria Fux, whose objective is to pay attention to theimpact of dance therapy practices and whether they can already be observed in the short term the life of the modern woman. Wasgiven by choice, adaptation and application of slogans stimulus that State network of teachers from Curitiba / PR, vivenciassem intheir bodies the effects of this practice which consists of a self resource, which benefits focuses on allowing the individual find thereal causes of their difficulties, thus enabling the act in order to transform them, a contributing factor to the development of selfesteem,so necessary for the good life.